2012
DOI: 10.3109/02770903.2012.743149
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Peripheral Eosinophils Are Associated with New-Onset and Persistent Wheeze and Airflow Obstruction in World Trade Center-Exposed Individuals

Abstract: Background Exposure to World Trade Center (WTC) dust and fumes is associated with onset of asthma-like respiratory symptoms in rescue and recovery workers and exposed community members. Eosinophilic inflammation with increased lung and peripheral eosinophils has been described in subpopulations with asthma. We hypothesized that persistent asthma-like symptoms in WTC-exposed individuals would be associated with systemic inflammation characterized by peripheral eosinophils. Methods The WTC Environmental Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 55 publications
5
22
1
Order By: Relevance
“…Kazeros et al (2013) hypothesized that persistent asthma-like symptoms in WTC Dust-exposed individuals would be associated with systemic inflammation characterized by peripheral eosinophils. Their WTC Environmental Health Center (WTCEHC) patients underwent a standardized evaluation including questionnaires and complete blood count.…”
Section: Groups With Results Based On Clinical Observationsmentioning
confidence: 99%
“…Kazeros et al (2013) hypothesized that persistent asthma-like symptoms in WTC Dust-exposed individuals would be associated with systemic inflammation characterized by peripheral eosinophils. Their WTC Environmental Health Center (WTCEHC) patients underwent a standardized evaluation including questionnaires and complete blood count.…”
Section: Groups With Results Based On Clinical Observationsmentioning
confidence: 99%
“…While most participants with post-9/11 LRS experienced symptom resolution during the study period, LRS persisted for a nearly one-third of those with initial symptoms. Most (85%) participants with persistent LRS had normal spirometry at follow-up; however, more than half had abnormal IOS results, including elevated resistance (R 5 ) and frequency dependence of resistance (R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], suggesting that small airways dysfunction not detected on standard spirometry may underlie symptoms in this group. This was further supported by our finding that higher R 5 and R 5-20 values at exam 1 were associated with an increased odds of persistent LRS at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of disease is likely the result of chronic inflammation initiated by exposure to the dust and potentiated by host characteristics as demonstrated by induced sputum studies showing significantly increased percentages of inflammatory biomarkers, neutrophils, and eosinophils in those with high WTC‐exposure [Fireman et al, ] and by serum studies from blood drawn within 6 months of 9/11 showing elevated levels of known inflammatory biomarkers, such as macrophage derived chemokines, that were associated with increased risk of subsequent abnormal pulmonary function [Nolan et al, ]. The protease/anti‐protease imbalance defined by mild to moderate genetic deficiency of alpha‐1 antitrypsin deficiency [Banauch et al, ] and the elevated set‐points of eosinophils and IgE levels observed in those with non‐resolving upper and lower airways inflammation [Kazeros et al, ; Kwon et al, ] are intrinsic characteristics of patients that can be assessed repeatedly using inexpensive, commercially available techniques. As the association between WTC‐exposure and disease diminishes over time, these and other innate biomarkers of risk for immune injury will become important for stratification of WTC‐exposed rescue/recovery workers.…”
Section: Discussionmentioning
confidence: 99%